Criminal humanitarianism. A visual exploration of criminal legitimisation, between alternative moralities and the political vacuum - CARNEVALE, DAVIDE NICOLA (Interdisciplinary Political Studies, 2018)
This article pledges to pursue three different, but closely correlated, lines of investigation related to the pro- cesses of legitimising contemporary criminal organizations. Starting from the analysis of visuals related to two regional contexts, Mexico and southern Italy, it explores how criminals engage in moral self-promotion, philanthropy, and other social practices through which criminal groups seek their own humanisation, mythi- cisation and sanctification. Observing two fields of criminal practices and symbolic production, with their capabilities of cultural sedimentation and social structuring, it explores the fil rouge weaving together the logic of promoting the internal cohesion of group with the mechanisms of external recognition. A more gen- eral reflection about the role of criminal organizations at the margins of neoliberal economies will be con- ducted by reviewing and analysing episodes of narco-charity, controversial connections between mafia bosses and local priests, business initiatives sponsored by criminals, visuals representing ‘bad’ non-state actors (out- laws) doing ‘good’ things.<br /